HEMOSTATIC SYSTEM DISORDERS IN CHILDREN WITH HYDRONEPHROSIS AND WAYS OF DRUG THERAPY - V.A. Dudarev; E.V. Portnyagina; A.G. Timofeeva; I.V. Kirgizov (Union of pediatricians of Russia, 2011)
In hydronephrosis, dysplasia of connective tissue results in hemostatic system disorders manifesting themselves as hemorrhagic mesenchimal dysplasia. The article analyses the coagulograms of 63 children with renal hydronephrosis in pre-school age. The work reviews the methods of diagnosing hemostatic disorders in moderate and severe dysplasia of renal parenchyma and ways of modern adequate drug therapy for these conditions. This method makes a prognosis of the disease more predictable and manageable.Key words: hydronephrosis, dysplasia, kidneys, children.